2018
DOI: 10.3390/nu10070922
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Intake of Chia Seed Is Associated with Increased Bone Mineral Content and Improved Hepatic and Intestinal Morphology in Sprague-Dawley Rats

Abstract: Chia seeds (Salvia hispanica) provide an unusually high content of α-linolenic acid with several potential health benefits, but few studies have examined the long-term intake of n-3 fatty acid-rich plant foods such as chia. In this work, we investigated some of the effects of a diet containing 10% chia seeds versus a conventional isocaloric diet for 10 and 13 months on body measurements, musculoskeletal system, the liver, and the intestines of 20 male Sprague-Dawley rats assigned into two groups. The n-6/n-3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 89 publications
(111 reference statements)
3
17
0
2
Order By: Relevance
“…However, in another investigation, chia flour did not reduce the weight of Wistar rats fed with a high-fat diet (HFD) (da Silva et al, 2016a;Marineli et al, 2015a). It has also been reported that chia seed consumption for 13 months increased the body weight in rats as compared to a control group (Montes Chañi et al, 2018;Poudyal et al, 2012). Although chia seeds increased the weight in rats fed a HFD, it also reduced the visceral adiposity index and decreased the retroperitoneal and omental fat depositions (Poudyal et al, 2012).…”
Section: Anthropometricsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in another investigation, chia flour did not reduce the weight of Wistar rats fed with a high-fat diet (HFD) (da Silva et al, 2016a;Marineli et al, 2015a). It has also been reported that chia seed consumption for 13 months increased the body weight in rats as compared to a control group (Montes Chañi et al, 2018;Poudyal et al, 2012). Although chia seeds increased the weight in rats fed a HFD, it also reduced the visceral adiposity index and decreased the retroperitoneal and omental fat depositions (Poudyal et al, 2012).…”
Section: Anthropometricsmentioning
confidence: 91%
“…Despite the high concentration of minerals in chia seed, its consumption by Wistar rats for 35 days revealed lower calcium balance and lower calcium absorption and retention rates in comparison with the group of animals that received calcium carbonate (control group) (da Silva et al., ). However, male Sprague‐Dawley rats fed a longer term (13 month) with 10% chia seed, versus a conventional isocaloric diet, showed higher bone mineral content and improved morphology of hepatocytes and gut tissue (Montes Chañi et al., ). This study provided new data suggesting the potential benefits associated with the long‐term intake of chia seed.…”
Section: Bioactive Compounds Of Chiamentioning
confidence: 99%
“…In this context, Ferreira et al [35] have reported that the dietary intake of chia seed reverses a sucrose-rich diet-induced adipose tissue dysfunction and insulin resistance in rats. In addition, Chani et al [36] reported that the long term intake of chia seed lowers the lipid deposit in hepatocytes and increases the intestinal muscle layer and crypt size in Sprague-Dawley rats.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Ferreira et al [35] have reported that the dietary intake of chia seed reverses a sucrose-rich diet-induced adipose tissue dysfunction and insulin resistance in rats. In addition, Chani et al [36] reported that the long term intake of chia seed lowers the lipid deposit in hepatocytes and increases the intestinal muscle layer and crypt size in Sprague-Dawley rats. A protein expression analysis of chia seed-treated adipocyte secreted microparticles showed decreased levels of insulin resistance and macrophage lipid accumulation related proteins such as LTB4, STAT6, IL-4 and TNF-α (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…Long-term dietary intake of chia seeds has been associated with increased bone health in Sprague-Dawley rats (42). High intake of omega-3 has in fact growing evidence of affecting bone metabolism.…”
Section: Discussionmentioning
confidence: 99%